2014
DOI: 10.1155/2014/964275
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Technical Efficiency of Creative Human Capital in China by Three-Stage Data Envelopment Analysis Model

Abstract: Previous researches have proved the positive effect of creative human capital and its development on the development of economy. Yet, the technical efficiency of creative human capital and its effects are still under research. The authors are trying to estimate the technical efficiency value in Chinese context, which is adjusted by the environmental variables and statistical noises, by establishing a three-stage data envelopment analysis model, using data from 2003 to 2010. The research results indicate that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Ma et al (2014) made an empirical analysis of creative HC technical efficiency of 31 provincial districts in China from 2003 to 2010 by using a three-stage DEA method and got three main conclusions. First, through the measurement and comparison of the technical efficiency level of creative HC among different districts, the current level of comprehensive technical efficiency among different districts in China is relatively high but has not reached the optimal level and still has room to improve.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma et al (2014) made an empirical analysis of creative HC technical efficiency of 31 provincial districts in China from 2003 to 2010 by using a three-stage DEA method and got three main conclusions. First, through the measurement and comparison of the technical efficiency level of creative HC among different districts, the current level of comprehensive technical efficiency among different districts in China is relatively high but has not reached the optimal level and still has room to improve.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with studies dividing China into eastern, middle, and western areas [33,34], this regionalism appears more targeted when crop production is the focus of research.…”
Section: Methodsmentioning
confidence: 99%
“…When regional results are considered, only the consumption area has a positive, but not significant, output elasticity of labor input, while the production area and the balanced area have negative ones. This robust result implies that there is surplus labor in rural China, and increasing the quantity of labor input in crop production alone cannot necessarily lead to output growth, but studies have suggested a positive effect of ameliorating the quality of labor resources on yields growth [34].…”
Section: Output Elasticity Of Input Factorsmentioning
confidence: 99%
“…It is generally accepted that human capital is a reflection of the quality of labor capital, and human capital consists of economic value of knowledge, technology, ability, and healthy quality which condenses on laborers (Yang et al, 2006). Human capital usually has greater appreciation of space than material capital and other production factors, especially in the post industry era and in the stage of rapid economic knowledge development (Ma et al, 2014). The modern stage of economic transformations is characterized by the fact that human capital becomes the main value of the company, the defining factor for sustainable development and economic growth as the competitive advantages of modern firms, which are currently achieved mainly not through material resources, but at the expense of knowledge, information and innovation, which is owned by people.…”
Section: Introductionmentioning
confidence: 99%